Performance Assessment of Iraq's Economy on the ease of doing business index: comparative study with KSA and UAE for 2004 – 2021 (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research critically examines Iraq's performance on the Ease of Doing Business Index (EDBI) compared to the experiences of Saudi Arabia and the United Arab Emirates (UAE), two regional leaders in reforming business environments. With Iraq ranked 172 out of 192 countries, it faces significant bureaucratic and regulatory challenges that impede foreign investment and private sector growth. In contrast, Saudi Arabia ranked 63 globally, has made substantial reforms under Vision 2030, while the UAE, at 16 globally, continues to set benchmarks through advanced infrastructure, streamlined processes, and progressive economic policies.Iraq underperforms in all, particularly in obtaining credit (186 globally) and enforcing contracts (147 globally), reflecting systemic inefficiencies and a lack of robust institutional frameworks. Conversely, Saudi Arabia's ongoing reforms and the UAE's high rankings demonstrate the effectiveness of policy-driven improvements in fostering entrepreneurship and investment.Notably, while the EDBI was discontinued in 2021 due to criticisms of its limited scope—excluding informal barriers like corruption—its insights remain valuable for diagnosing Iraq’s challenges. Drawing from Saudi and Emirati experiences, the study recommends actionable economic policies tailored for Iraq: implementing centralised digital systems to streamline business registration, reforming tax and insolvency laws, enhancing investor protections, and modernising trade infrastructure. These reforms aim to address Iraq's regulatory bottlenecks, fostering a more conducive environment for entrepreneurship and economic growth.